1994
DOI: 10.1007/bf00202812
|View full text |Cite
|
Sign up to set email alerts
|

Numerical chromosome abnormalities in spermatozoa of fertile and infertile men detected by fluorescence in situ hybridization

Abstract: Fluorescence in situ hybridization (FISH) with single-color chromosome-specific probes was used to study the rates of disomy for chromosome 1, 16, X, and Y in sperm of fertile and infertile subjects. Diploidy rates were studied using a two-color cocktail of probes for chromosomes 17 and 18 in the same sperm samples. Two-color methodology was not available at the outset of the study. A total of 450,580 spermatozoa were studied from 21 subjects (9 fertile, 12 infertile). Significant differences were observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
77
4
3

Year Published

1996
1996
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 26 publications
8
77
4
3
Order By: Relevance
“…Our results are in accordance with the data of many other studies that reported significant negative correlations between sperm concentration and the mean frequency of disomy, especially for the sex chromosomes [6,10,15,21,22]. However, other studies did not show a significant correlation between sex disomy rates and sperm concentration [3,20,23,24]. The disparate results of these studies might be related to their investigation of different types of male infertility: in the majority of cases oligozoospermia was associated with one or more abnormal other parameters.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results are in accordance with the data of many other studies that reported significant negative correlations between sperm concentration and the mean frequency of disomy, especially for the sex chromosomes [6,10,15,21,22]. However, other studies did not show a significant correlation between sex disomy rates and sperm concentration [3,20,23,24]. The disparate results of these studies might be related to their investigation of different types of male infertility: in the majority of cases oligozoospermia was associated with one or more abnormal other parameters.…”
Section: Discussionsupporting
confidence: 90%
“…The disparate results of these studies might be related to their investigation of different types of male infertility: in the majority of cases oligozoospermia was associated with one or more abnormal other parameters. In addition the classification criteria of individuals appeared to be subjective and no mention was made of the characteristics of the sperm in the study of Miharu et al [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disomy rate (0.38%) for chromosome 1 in this study is similar to that (0.41%) in the report of Guttenbach and Schmid (1991), while higher than those in the previous reports (Robbins et aL, 1993;Miharu et al, 1994) (Table 5). The disomy rate (0.39%) for chromosome 17 in this study is comparable to those (0.33% and 0.31%) by Han et al (1992) and by Guttenbach et aL (1994a), while higher than that (0.13%) in the report of Bischoff et al (1994) (Table 5).…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the hamster egg may act as a barrier against some sperm with chromosomal abnormalities. In order to know an effect of infertility status on cytogenetic abnormality of sperm, Miharu et al (1994) studied disomy frequencies both in infertile and fertile populations, and could not find any differences between the two populations. However, Wyrobek et al (1994) did not find any differences in the frequencies of disomic sperm between FISH and karyotype studies using the hamster egg test.…”
Section: Discussionmentioning
confidence: 99%